Pengaruh Profitabilitas, Leverage, dan Kebijakan Dividen Terhadap Harga Saham: (Studi Pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022) - Erlangga, Afrizal Septian; Mahardika, Dewa Putra Khrisna (eProceedings of Management, 2024)
Since the share price is a representation of a firm's worth, higher share prices correspond to higher companyvalues. Although supply and demand in the capital market might influence stock prices, the company's long-termgoal in issuing these shares is undoubtedly to raise funds. Determining the impact of leverage, dividend policy,also profitability on the share price of the food and beverage subsector written on the IDX between 2018 and2022 is the goal of this study. The study population consisted of firms in the food and beverage sub-sector thatwere written on the IDX and provided financial statements for the years 2018 through 2022. The sample used inthis research includes thirteen companies over a five-year period, with data analyzed using sixty-five data pointsusing a technique called purposive sampling. This study use the regression analysis of panel data method.According to the study's findings, the factors of profitability, leverage, also dividend policy all have a majorimpact on the share price of firms in the food and beverage subsector that are written on the IDX between 2018and 2022. For the food and beverage sub-sector written on the IDX in 2018–2022, the leverage variable anddividend policy have no substantial impact on stock prices; only the profitability variable has a partial effect onstock prices. It is advised that future researchers use alternative business sectors for their examinations of theindependent and dependent variables, or use different independent variables within the same firm sector. Keywords-dividend policy, leverage, profitability, share price